Evaluation of the Rectal Cancer Patient Decision Aid: A Before and After Study. Issue 3 (March 2016) - Wu, Robert Chi; Boushey, Robin Paul; Scheer, Adena Sarah; Potter, Beth; Moloo, Husein; Auer, Rebecca; Tadros, Shaheer; Roberts, Patricia; Stacey, Dawn
Abstract : BACKGROUND: In rectal cancer surgery, low anterior resection and abdominoperineal resection have equivocal impact on overall quality of life. A rectal cancer decision aid was developed to help patients weigh features of options and share their preference. OBJECTIVE: The aim of this study was to evaluate the effect of a patient decision aid for mid to low rectal cancer surgery on the patients' choice and decision-making process. DESIGN: A before-and-after study was conducted. Baseline data collection occurred after surgeon confirmation of eligibility at the first consultation. Patients used the patient decision aid at home (online and/or paper-based formats) and completed post questionnaires. SETTING: This study was conducted at an academic hospital referral center. PATIENTS: Adults who had rectal cancer at a maximum of 10 cm proximal to the anal verge and were amenable to surgical resection were considered. Those with preexisting stoma and those only receiving abdominoperineal resection for technical reasons were excluded from the study. INTERVENTION: Patient with rectal cancer were provided with a decision aid. MAIN OUTCOME MEASURES: The primary outcomes measured were decisional conflict, knowledge, and preference for a surgical option. RESULTS: Of 136 patients newly diagnosed with rectal cancer over 13 months, 44 (32.4%) were eligible, 36 (81.9%) of the eligible patients consented to participate, and 32 (88.9%) patients completed the study. The mean age of participants was 61.9 ± 9.7 years and tumor location was on average 7.3 ± 2.1 cm above the anal verge. Patients had poor baseline knowledge (52.5%), and their knowledge improved by 37.5% ( p < 0.0001) after they used the patient decision aid. Decisional conflict was reduced by 24.2% ( p = 0.0001). At baseline, no patients preferred a permanent stoma, and after decision aid exposure, 2 patients (7.1%) preferred permanent stoma. Over 96% of participants would recommend the patient decision aid to others. LIMITATIONS: This study was limited by the lack of control for potential confounders and potential response bias. CONCLUSIONS: The patient decision aid reduced decisional conflict and improved patient knowledge. Participants would recommend it to other patients with rectal cancer. Abstract : Supplemental Digital Content is available in the text.